THE IMPACT OF THE PROBABILITY DISTRIBUTION FUNCTION FOR THE RANDOM VARIABLES COMPRESSIVE STRENGTH OF CONCRETE AND YIELD STRESS OF STEEL IN THE RELIABILITY ANALYSE (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The aim of this study is to evaluate the variation of the index of reliability sist of a reinforced concrete beam, strengthened with Carbon Fiber Reinforced Polymer ”“ CFRP, considering two different probability distribution functions ”“ PDF for the random variables ”“ concrete compressive strength c f and steel yield stress s f , and two different configurations of reinforcement with CFRP. In the first analyze the sist is evaluated twice, initially using the Normal PDF for the cf and the s f , as considered by the Brazilian code ”“ NBR 6118:2014, afterward the same index of reliability is obtained again, this time considering the Lognormal PDF for both materials, as considered by the Joint Committee on Structural Safety ”“ JCSS. The beam is strengthened with longitudinal CFRP reinforcement Afl and transversal CFRP reinforcement Aft. In the second analyze the efficiency of the new reinforcement is evaluated. This time the beam is strengthened with either Afl or Aft , and the probability distribution functions PDF for the concrete and steel are considered to be Lognormal For the two sets of reliability analyses the beam is subjected to a torsional moment, and the methodology and reinforcement configurations are the same developed by Silva Filho (2007).